A relational typology of project management offices - Müller, Ralf; Glückler, Johannes; Aubry, Monique (Project management journal, 2013)
This explorative article develops a relational typology of PMOs based on their roles with stakeholders. A multi-case study was used to identify the roles of PMOs in multiple-PMO settings. A three-dimensional role space allows locating the complex relational profiles that PMOs take on with respect to their stakeholders in practice. Superordinate, subordinate, and coequal roles were identified in a framework of servicing, controlling, and partnering in organizations. While servicing (subordinate role profile) and controlling (superordinate role profile) support organizational effectiveness and exploitation of knowledge, partnering (coequal role profile) creates the slack necessary for potential exploration of new knowledge.
Gesehen am 06.07.2021